Modeling of microporosity formation during solidification of aluminum alloys. Issue 1 (May 2015) - Wang, T; An, D; Zhang, Q; Dai, T; Zhu, M
Abstract: A two-dimensional (2D) multi-phase cellular automaton (MCA) model is adopted to simulate the dendrite and microporosity formation during solidification of aluminium alloys. The model involves three phases of liquid, gas, and solid. The effect of liquid-solid phase transformation on the nucleation and growth of porosity, the redistribution and diffusion of solute and hydrogen, and the effects of surface tension and environmental pressure are taken into account. The growth of both dendrite and porosity is simulated using a CA approach. The diffusion of solute and hydrogen is calculated using the finite difference (FD) method. The simulations can reveal the interactive and competitive growth of dendrites and micropores, and the microsegregationof solute and hydrogen. The porosity nuclei with large size are able to grow preferentially, while the growth of the small porosity nuclei is inhibited. Gas pores grow spherically when it is enveloped by liquid. After touching with dendrites, the shapes of pores become irregular. An increased initial hydrogen concentration reduces the incubation time of porosity nucleation, but increases the final percentage of porosity and the average porosity size at the eutectic temperature. With cooling rate decreasing, the competitive growth between gas pores becomes more evident, leading to non-uniform porosity sizes, and more irregular morphology of the porosities with larger size. The simulation results are compared reasonably well with the experimental data reported in literature.